2015
DOI: 10.1007/s10815-015-0535-x
|View full text |Cite
|
Sign up to set email alerts
|

Air quality in the assisted reproduction laboratory: a mini-review

Abstract: Quality of air in the clinical embryology laboratory is considered critical for high in vitro fertilization (IVF) success rates, yet evidence for best practices is lacking. Predominantly anecdotal reports on relationships between air quality and IVF success rates have resulted in minimal authentic clinical laboratory guidelines or in recommendations that are based on industrial cleanroom particulate standards with little attention to chemical air filtration. As a result, a nascent industry of costly, specializ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 42 publications
0
25
0
2
Order By: Relevance
“…Albumin is the most abundant protein in the oviduct (Leese, 1988) and thus the most common protein used in culture media. Albumin serves many functions, most notably as an antioxidant (Bavister, 1995;Morbeck, 2015). Lot-tolot variations exist with human serum albumin (HSA) (Swain, 2015), particularly with respect to the stabilizer octanoic acid (Fredrickson et al, 2015;Leonard et al, 2013).…”
Section: Culture Media -General Composition and Protein Supplementationmentioning
confidence: 99%
“…Albumin is the most abundant protein in the oviduct (Leese, 1988) and thus the most common protein used in culture media. Albumin serves many functions, most notably as an antioxidant (Bavister, 1995;Morbeck, 2015). Lot-tolot variations exist with human serum albumin (HSA) (Swain, 2015), particularly with respect to the stabilizer octanoic acid (Fredrickson et al, 2015;Leonard et al, 2013).…”
Section: Culture Media -General Composition and Protein Supplementationmentioning
confidence: 99%
“…On the other hand, IAQ should be monitored to minimise the impact the laboratory experiments' samples. For instance, IQ is extremely significant in the clinical embryology laboratory activities and is recognised as a significant parameter which influences in vitro fertilisation (IVF) success levels [57].…”
Section: Laboratory Environmental Conditionsmentioning
confidence: 99%
“…25,26 Recently, attention has been focused on VOCs and their role on in vitro human embryo cultures. 27,28 As the practices of IVF evolve toward the transfer of embryos at the blastocyst stage and the use of trophectoderm biopsy for preimplantation genetic testing (PGT), the extended period of in vitro culture required depends on a favorable and stable environment based on high-quality ambient air. 28 A study conducted by Choe et al 29 investigated the association between air pollutant levels and intrauterine pregnancy per cycle in women undergoing one or more in vitro fertilization procedures.…”
Section: Air Contaminants and The Impact On Embryo Quality And Pregnamentioning
confidence: 99%
“…27,28 As the practices of IVF evolve toward the transfer of embryos at the blastocyst stage and the use of trophectoderm biopsy for preimplantation genetic testing (PGT), the extended period of in vitro culture required depends on a favorable and stable environment based on high-quality ambient air. 28 A study conducted by Choe et al 29 investigated the association between air pollutant levels and intrauterine pregnancy per cycle in women undergoing one or more in vitro fertilization procedures. This study has shown that exposure to VOCs during ovarian stimulation and embryo transfer is associated with decreased intrauterine pregnancy in IVF cycles.…”
Section: Air Contaminants and The Impact On Embryo Quality And Pregnamentioning
confidence: 99%
See 1 more Smart Citation